ANALISIS KESALAHAN PENGGUNAAN SISTEM KALA PADA PEMBELAJAR BAHASA JEPANG TINGKAT DASAR DI INDONESIA - Suhartini, Suhartini (Universitas Diponegoro, 2016)
(Title: An Analysis of The Errors of Using Tenses On Basic Japanese Learners In Indonesia.) The research aims at describing the errors of using tenses in basic Japanese on learners whose first language is Bahasa Indonesia. In the process of acquiring the second language, it is possible for the first language to influence the second one because of the transfer of some fundamental elements, i.e. using tenses of the first to the second language. The data of research are in form of Japanese language sentences that get interference of tenses formation from Indonesian language. The data were collected by observation. Contrastive method was used in analysis. The results of the analysis show that Bahasa Indonesia tenses formation system influences the use of using tenses in basic Japanese on those who learn Japanese as a second language. The lead to the errors in using tenses in Japanese. To overcome the problem, Japanese teachers shall expose the using tenses continuously to its lerners whose first language is bahasa Indonesia. <a href=